2017
DOI: 10.1016/s2055-6640(20)30331-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with intention to take non-occupational HIV post-exposure prophylaxis among Thai men who have sex with men

Abstract: Background Men who have sex with men (MSM) are disproportionately infected with HIV in Thailand. Factors affecting their intention to take non-occupational HIV post-exposure prophylaxis (nPEP) are not well understood. This study sought to determine factors associated with an intention to take nPEP in this population. Method This is a two-phase mixed-method study. Phase I was a cross-sectional survey of intention to take nPEP in 450 MSM attending for HIV testing, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…One nPEP recipient was found subsequently seroconverted to HIV at 3-month after exposure due to ongoing high-risk behaviors, not ascribed as nPEP failure, as observed in other similar studies. [ 51 , 57 ] There is something noticeable that 46 participants’ source contact had been confirmed as HIV positive, and 44 nPEP users were tested as negative during the repeating HIV serology, except for 2 not complying with the follow-up appointment. All again testify that nPEP, one of several biomedical HIV prevention strategies, is truly effective in real-world settings.…”
Section: Discussionmentioning
confidence: 99%
“…One nPEP recipient was found subsequently seroconverted to HIV at 3-month after exposure due to ongoing high-risk behaviors, not ascribed as nPEP failure, as observed in other similar studies. [ 51 , 57 ] There is something noticeable that 46 participants’ source contact had been confirmed as HIV positive, and 44 nPEP users were tested as negative during the repeating HIV serology, except for 2 not complying with the follow-up appointment. All again testify that nPEP, one of several biomedical HIV prevention strategies, is truly effective in real-world settings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies checked whether self-reported knowledge about PEP was accurate or evaluated PEP knowledge in MSM. Those MSM who were aware of PEP had adequate knowledge about PEP; however, less than half of them correctly answered that PEP needs to be taken for 28 days (30,34). Among 94 MSM who had heard of PEP, 11% were concerned about side effects; most (68%) felt they would know how to get PEP, and nearly two-thirds anticipated that they would not be able to afford it (8).…”
Section: Awareness Of Pepmentioning
confidence: 99%
“…Individual factors Concern about side effects (8) Having been involved in high-risk sexual intercourse (37,39) Lack of PEP information (11,34) Using methamphetamine (11) Having an adequate knowledge about PEP Knowledge where to get PEP (30,36,43)…”
Section: Domains Barriers References Facilitating Factors Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that nPEP use might influence nPEP knowledge, and it might influence anticipated individual and population behavioral changes and discrepancy directly and indirectly. People generally first learn about HIV, and then nPEP [ 23 ], and HIV and nPEP knowledge were associated with an intention to use nPEP [ 24 ]. In this regard, we hypothesize that HIV knowledge might have an effect on nPEP knowledge, and it might influence anticipated individual and population behavioral changes and discrepancy directly and indirectly.…”
Section: Introductionmentioning
confidence: 99%